Macroscopic evaluation of the gut associated lymphoid tissues (GALT) of the small intestine of three-month-old calves - Saw, Po Po; Abu Bakar @ Zakaria, Md Zuki; Saad, Mohd Zamri; Omar, Abdul Rahman; Abd Wahid, Mohd Effendy (Universiti Putra Malaysia Press, 2004)
Gut associated lymphatic tissues (GALT) play a major role in intestinal immunity. The GALT are portal of entry for significant pathogens. Three calves of three-month-old were slaughtered and the small intestines were removed for macroscopic evaluation. The Peyer’s patches were located on the anti-mesenteric borders of duodenum, jejunum and ileum. The distal part of duodenum and whole of jejunum consist of discrete Peyer‘s patches (DPPs), while the ileum has only continuous Peyer‘s patches (CPPs). The mucosal folds are thicker in these regions. The number and size of discrete Peyer’s patches vary in different parts of small intestine and in individual calf of the same age. Peyer’s patches of proximal parts of jejunum were mostly oval, elongated and irregular shaped. The whole ileum was occupied by the continuous Peyer‘s patches. The number of discrete Peyer‘s patches (DPPs) in jejunum ranged from 30 to 50. The distance between each discrete Peyer’s patches and their sizes were not significantly (p<0.05) different.